Pedestrian safety at junctions - Wee, Jing Ying (2016)
With the growing affluence and standard of living of Singaporeans, there has been an increasing demand for more transportation. This has caused a rise in vehicles on the road, exposing road users to more dangers. Concerns regarding pedestrian safety at junction have always been in the spotlight whenever an accident occurs, especially accidents which involves the “turning traffic give way the pedestrians” scheme. This study investigates the serious and fatal road accidents involving pedestrians at junctions in Singapore in 2014. The characteristics of accidents analysed includes the type of vehicle, type of collision at the T-junction, as well as the reasons which resulted in an accident involving pedestrians. Data were collected from the Singapore Traffic Police Headquarters and were classified into 3 categories: vehicle classification, type of collision and reasons for the accidents that are occurring at the junctions. Spearman’s correlation coefficient method was used to determine if the rate of accident is dependent on the type of vehicle involved. Analysis from the 39 cases indicated that the scheme may be dangerous but not to the point of abolishment. The data also highlighted some issues such as driver’s fatigue and blind spots. Mitigating solutions were then suggested to improve the current scheme.